A quantitative assessment of body iron status and its relationship with glycemic control in patients of type 2 diabetes mellitus in a tertiary care hospital of Kolkata - Saha, Ananya; Mukhopadhyay, Pradip; Nath, Indrajit; Kumar, Arun; Biswas, Utpal Kumar (Asian Journal of Medical Sciences, 2021)
Background: Diabetes is one of the most common disease which is observed in every household of Indian population. The longevity of the diabetic patients is dependent upon the frequency of complication and comorbidity that they encounter. Serum iron and ferritin, both being the aggravators to the oxidative stress accelerating the development of complications, gives us the reason to venture into the territory exploring the possibility of monitoring the body iron stores and taking prevent measures to control such complication. The current study was designed with an aim to knot the relationship between body iron stores and glycemic control in patients of type-II diabetes mellitus. Aims and Objectives: To measure the levels of serum ferritin, serum Iron, transferrin saturation and HbA1C and finding out the relationship between body iron stores and glycemic control in patients of Type-II Diabetes Mellitus. Materials and Methods: A total of 50 diagnosed cases of type II DM and 50 healthy controls between the age group of 35-65 years were taken following inclusion and exclusion criteria. Body iron stores were assessed by measuring serum ferritin, Serum iron and Transferrin saturation and Glycemic control was assessed by measuring levels of HbA1C. Results: A significant increase in serum ferritin, serum iron and Transferrin saturation (P<0.001) was noted in diabetic patients as compared to controls. There was a positive correlation between serum iron and transferring saturation in the diabetic patients. Conclusion: The co-morbidities and complications in the Diabetic population can be prevented by monitoring Body iron stores as they can significantly contribute to the oxidative stress leading to the complication and decreased life expectancy. Early detection in the abnormality in the body iron store can help us in employing proper measures for a better management of Type-II diabetic patients and thereby improving their survival.